Ba0.95Ca0.05Ce0.9Y0.1O3 as an electrolyte for proton-conducting ceramic fuel cells. (1st May 2019) - Dudek, M.; Lis, B.; Lach, R.; Daugėla, S.; Šalkus, T.; Kežionis, A.; Mosiałek, M.; Socha, R.P.; Morgiel, J.; Gajek, M.; Sitarz, M.; Ziąbka, M.
Abstract: Comparative studies of the physicochemical and electrochemical properties of BaCe0.9 Y0.1 O3 and Ba0.95 Ca0.05 Ce0.9 Y0.1 O3 sintered ceramics are described. The orthorhombic (Pnma) space group was determined for both investigated samples within the temperature range 25–800 °C, using the X-ray diffraction method. A decrease in the cell volume of Ba0.95 Ca0.05 Ce0.9 Y0.1 O3 compared to that of BaCe0.9 Y0.1 O3 was observed within the investigated temperature range. It was found that the partial substitution of calcium for barium, resulting in Ba0.95 Ca0.05 Ce0.9 Y0.1 O3, caused an increase in specific free volume and global instability index compared to the original composition BaCe0.9 Y0.1 O3 . Improvement of the chemical resistance of Ba0.95 Ca0.05 Ce0.9 Y0.1 O3 in a CO2 gas atmosphere was observed. It was found that Ba0.95 Ca0.05 Ce0.9 Y0.1 O3 exhibited a slightly lower level of electrical conductivity than BaCe0.9 Y0.1 O3 in air as well as in ArH2 gas atmospheres. The greater chemical resistance of Ba0.95 Ca0.05 Ce0.9 Y0.1 O3 in a CO2 gas atmosphere enhances the suitability of the modified material as an electrolyte for fuel cells with proton-conducting ceramics. The electrochemical response of the interface (La0.60 Sr0.40 )0.95 Co0.20 Fe0.80 O3−δ |Ba0.95 Ca0.05 Ce0.9 Y0.1 O3 was also investigated within the applied potential range from −0.05 to −0.5 V in SOFC mode as well as from 0.05 to 0.5 V in SOEC mode); it was found that the current reached a fairly stable value over time.